First detection of Aspergillus fumigatus azole-resistant strain due to Cyp51A TR46/Y121F/T289A in an azole-naive patient in Spain - Pelaez, T. (New Microbes New Infect, 2015)
We report the first isolation of a voriconazole-resistant Aspergillus fumigatus strain harbouring the azole resistance mechanism TR46/Y121F/T289A, recovered from an azole-naive patient in Spain with chronic obstructive pulmonary disease. This new finding in Spain suggests the spread of this resistance mechanism and reinforces the need for antifungal susceptibility surveillance.